Cultural Constructs of Prosperity and their Influence on Childhood Obesity in India (Journal of Advances and Scholarly Researches in Allied Education, 2026)
This paper explores the impact of cultural constructs of prosperity on childhood obesity in India, emphasizing how traditional beliefs about body size influence feeding practices. The purpose of this study was to analyse the ways in which societal beliefs that view a larger body as synonymous with health and success contribute to the growing incidence of obesity among youngsters. The research was conducted using a technique that was based on reviews, and it relied entirely on secondary sources such as reports from the government for health, articles from academic journals, and previously published literature. Through the process of synthesising data from these many sources, the study was able to give insights into the ways in which cultural values influence the feeding behaviours of parents, which in turn leads to children engaging in unhealthy eating habits and overeating.The most important findings demonstrated that cultural ideas have a significant impact on the way Indian families see the health of their children, frequently placing a higher value on the size of the child's body than on the quality of their nourishment. Due to the fact that these attitudes contribute to poor feeding practices, which, when combined with the growing urbanisation and availability of foods that are high in calories, add to the problem of childhood obesity. In addition, the study brought attention to the necessity of public health programs that are sensitive to cultural norms and that are in line with traditional values while also encouraging better lifestyles. In addition, for the purpose of addressing the misunderstandings that exist regarding diet and body size, educational activities that are directed towards parents and carers were proposed.Due to the fact that the study only used secondary sources of data, it was classified as a theoretical analysis. Although this method offered a comprehensive grasp of the matter, it also highlighted the importance of conducting more research in the future that makes use of primary data in order to obtain real-time perspectives on cultural effects. In order to construct successful public health strategies to prevent childhood obesity in India, it is essential to have a solid understanding of these cultural characteristics. This will ensure that treatments are both relevant and durable in a variety of socio-cultural situations.